ASSESSMENT OF THE STATE OF SOME ANTI-EROSION INSTALLATIONS IN THE DAIRA OF HONAINE (WILAYA OF TLEMCEN – ALGERIA) - Nadia Zekri; Nesrine Bellahreche (International Journal of Innovative Technologies in Social Science, 2025)
Water erosion is responsible for the degradation of more than half of the world’s soils. In northern Algeria, it is widespread, particularly in the western region, which requires mechanical and biological developments to control it. The objective of this work is to evaluate the state and effectiveness of some anti-erosion developments, carried out in a coastal region: that of the Daira de Honaine (wilaya of Tlemcen). The methodology adopted was based on direct field observations, photo taking and data collection at the Forest Conservation in the wilaya of Tlemcen and the district of Remchi. The results obtained showed that most of the anti-erosion installations, carried out in 5 stations in the study region, are in very good condition. This demonstrates the perseverance of foresters, particularly in the creation of gabion thresholds and ridges, as well as the will of farmers in the good management and conservation of agricultural lands.